Regulation of runt transcription by Drosophila segmentation genes. - Klingler, M.; Gergen, J.P. (Mechanisms of Development, 1993)
The runt gene plays an important role in the genetic hierarchy that generates the segmented body pattern during the early stages of Drosophila embryogenesis. We studied mRNA expression in mutant embryos in order to investigate the regulation of runt transcription during these stages. We used sensitive whole-mount in situ hybridization procedures to identify the earliest, and therefore most likely direct regulatory effects. There are several distinct phases of runt expression in the early embryo. We find that each phase depends on a different set of regulators. The first phase of expression is a broad-field of mRNA accumulation in the central regions of syncytial blastoderm stage embryos. This pattern is due to terminal repression by the anterior and terminal maternal systems. The effect of the terminal system, even at this early stage, is mediated by two zygotic gap genes, tailless and huckebein. A 7 stripe pattern of runt mRNA accumulation emerges during the process of cellularization. The initial formation of this pattern depends on position-specific repression by zygotic gap genes. Examination of the early RNA patterns of the pair-rule genes even-skipped, hairy, and fushi tarazu indicate that they are also regulated in a similar manner. Three pair-rule genes, hairy, even-skipped, and runt itself, also affect runt's 7 stripe pattern. The effects of runt are stripe specific; the effects of hairy are more uniform; and the patterns obtained in even-skipped mutant embryos show a combination of both stripe specific and uniform regulatory effects. A third distinct phase of expression occurs at the onset of gastrulation when runt becomes expressed in 14 stripes. fushi tarazu plays a negative regulatory role in generating this pattern, whereas the pair-rule genes paired and odd-paired are required for activating or maintaining runt expression during these stages.